Ramsar wetlands in the Mediterranean wetlands Committee countries - Η. Δημητριάδης; Α. Αποστολάκης; Ν. Κόντος; Ε. Φυτώκα; I. Dimitriadis; A. Apostolakis; E. Fitoka; N. Kontos (Ministry of Environment, Physical Planning and Public Works, 2001)
MEDWET